Biotransformation of rice husk, palm oil mill effluent and sewage sludge through bio composting / Nurjihan Binti Mohammad Nazara, Nurain Farahin Abdul Razak & Mohd Zaki Sukor - Mohammad Nazar, Nurjihan; Abdul Razak, Nurain Farahin; Sukor, Mohd Zaki
The present study investigated that rice husk make a potential fertilizers by bio-composting. Rice Husk was obtained from Kilang BERNAS, Paya Keladi, Pulau Pinang, while the POME were collected from Sime Darby Melaka, Malaysia and the sewage sludge were collected from Indah Water Konsortium, Johor Bahru. The organic waste were stored at temperature room,25°C in a storage. There are various experiments made using rice husk as main component to make a fertilizer by composting it with fruits bunch and worms. Besides that, other substance use to make a potential fertilizer is Palm Oil Mill Effluent (POME). POME contains several acidic nutrients needed to make a fertilizer. It is also used because of its high content of nitrogen. In addition, sewage sludge also use by various experiments to make a fertilizer. Sewage sludge contains high acidity which is good to make a better fertilizer. In this experiment, these three substances are used to make a fertilizer. Rice husk and the substituent mixed with ratio 1 :9. The substituents used in this were sewage sludge and POME with the ratio 70:30, 50:50 and 30:70 respectively. Besides , the mixture was stirred thoroughly in the containers. Then, the containers were place on a cover at an open field and were covered by a plastic bag. These containers were placed at the open field for 28 days to produce the result either in acidic or alkaline or both. After 28 days, there had a lot of changed in the mixture. The smelly became odourless, the colour became darkness, some of them were acidic and alkaline, the mixtures were composed roughly and it gave a different pH value for each of them. According to the result, Palm Oil Mill Effluents (POME) makes more acidic fertilizers than the Sewage sludge .Theoretically, the higher the acidic content in fertilizer the higher the quality of the fertilizers. Thus, higher POME content makes better fertilizers and it produced a healthy fertilizer for plant.